A Research on the Correlation between 21st Century Skills and English Reading Strategy of English Majors: A Quantitive Study in Chengdu University - Luo, Yanni (Pacific International Journal, 2022)
As it enters the twenty-first century, countries all over the world have developed in the field of 21st Century skills to adapt to global economic competition and technological advances. This study examines the relationship between English majors’ 21st-century skills and their use of English reading strategies quantitatively and qualitatively and provides corresponding helpful suggestions for optimizing their use of English reading strategies and innovating teachers’ English reading pedagogy.